Nonmaleficence in Paediatric Patients With Diarrhoea : A Concept Analysis - Salam, Wulan Anugrah Pauji; Awaludin, Sidik (LPPM STIKes Muhammadiyah Ciamis, 2025)
Diarrhoea is still a world health problem, from WHO data diarrhoea is the number one cause of death of toddlers Proper handling will minimise the occurrence of complications that will occur in children with diarrhoea, so the actions taken by nurses must be in accordance with existing procedures and not harm the patient.The purpose of concept analysis in this study was to obtain relevant definitions of non-maleficence in paediatric patients with diarrhoea.The concept analysis method in this study uses Walkers and Avants 2014. Databases that have been obtained from various sources including PUBMED, Google Scholar, by writing the keywords ‘Diarrhoea in Children’, ‘Nonmaleficence’, with the year of publication 2010 to 2024 in English or Indonesian. The principle of non-maleficence requires that every action does not harm or harm either physically or psychologically, and applies that the action taken must outweigh the harm received by the patient and not offend. The concept of non-maleficence used by nurses explaining to the patient's parents with simpler language